A contribution to the knowledge of Charletonia nazeleae (Acari: Erythraeidae) - Najmeh Kiany; Marjan Seiedy; Masoud Hakimitabar; Martin Husemann (Persian Journal of Acarology)
Larvae of Charletonia nazeleae Karimi Iravanlou, Kamali & Talebi were previously collected from Karaj, Alborz province, Iran, parasitizing two different acridid grasshopper species. Here, we present new morphological and meristic data based on collecting new mite specimens during surveys to Zagros Mountains, Fars province, Iran and a correction of the previous description by reconsidering the type specimen and augmenting the original data. Also, two new hosts for this species are identified.